Torsional behaviour of steel fibre-reinforced oil palm shell concrete beams - Yap, Soon Poh; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin; Khaw, Kuan Ren (Elsevier, 2015)
The increasing demand for curved structural members has prompted an increase in the research on the torsional behaviour of concrete. Recently, oil palm shell (OPS) has received considerable attention as a material that enables the production of sustainable lightweight concrete. This work investigated the effects of steel fibre of 0.25%, 0.50%, 0.75% and 1.00% volume fractions on the mechanical properties and torsional resistance of OPS concrete (OPSC) and OPS fibre-reinforced concrete (OPSFRC) beams. The experimental results showed that the increase in fibre content resulted in better mechanical properties and torsional resistance of OPSFRC. The compressive, splitting tensile and flexural strengths of OPSFRC with 1% steel fibres were found to be 40%, 110% and 150%, respectively, higher than the control mix. The crack bridging effect also improved the pre-cracking and post-cracking torsional behaviour of OPSFRC. The highest cracking torque, ultimate torque, twist at failure and torsional toughness of 8.3 kNm, 8.5 kNm and 1.31 kNm/m were obtained for the mix with 1% steel fibre. Moreover, the crack arrest ability of the steel fibre reduced the primary torsional crack widths and formed multiple fine cracks. Further, a simplified torsional model is proposed to predict the torsional behaviour of OPSC and OPSFRC. (C) 2015 Elsevier Ltd. All rights reserved.